2023
DOI: 10.4317/jced.59992
|View full text |Cite
|
Sign up to set email alerts
|

Diameter and taper variability of gutta-percha cones adapted to TruNatomyTM and RotateTM rotary file systems

Abstract: Background Evaluate the discrepancy in diameter and taper between adapted gutta-percha cones for TruNatomyTM 26.04 (TRU04), RotateTM 25.04 (ROT04) and 25.06 (ROT06) systems and their reference files. Material and Methods A sample of 60 gutta-percha cones and 15 rotary files was selected and divided into three groups (TRU04, ROT04, ROT06). Each group consisted of 20 cones and 5 corresponding files. They were observed under an optical microscope at x20 magnification and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A difference in the actual dimension of the endodontic rotary/reciprocating instruments and GP points dedicated to them was also observed [4,18,26,27]. Salles at al.…”
Section: Discussionmentioning
confidence: 93%
“…A difference in the actual dimension of the endodontic rotary/reciprocating instruments and GP points dedicated to them was also observed [4,18,26,27]. Salles at al.…”
Section: Discussionmentioning
confidence: 93%
“…Moulle et al [8] evaluated standardised GP points from six different manufacturers and found that some of them did not comply with the ISO standard. There are reports that bigger taper gutta-percha points dedicated to continuous rotational motion instrumentation, as well as for reciprocated systems, had larger diameters in relation to the corresponding endodontic instruments [1,7,10,11]. In another study, most of the bigger taper points of two different brands had larger dimensions than they should have been [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the dimensional tolerance does not apply to the tip of the point (D 0 ). A number of studies have reported the lack of standardisation of commercially available gutta-percha points with a wide variation in diameter and taper [1,7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%